Students' Attitudes and Behaviour towards the River and Activities of the Surrounding Communities - Novita Resti; Hertien Koosbandiah Surtikanti (Universitas Labuhanbatu, 2024)
Currently, there has been a lot of environmental damage due to human activities. Sand mining is one of the community activities in Indragiri that has caused various damages in the area around the river such as polluted river water, damaged roads due to frequent sand-carrying trucks, landslides due to erosion, and noise due to sand suction machine activities. If no efforts are made to manage the environment sustainably, this situation will get worse in the future. This condition encourages the need for efforts to minimise various environmental damages, one of which is through education. The purpose of this study is to analyse students' attitudes and behaviour towards the river environment so that the results of this analysis can be used as a basis for developing environmental education programs so that the program is right on target and according to needs. This survey research involved 151 students who were taken using purposive sampling. The instrument used was a questionnaire with 35 questions. Data analysis was done with descriptive quantitative. The results showed that; (1) students already have good positive attitudes towards the river; (2) most students already have good behaviour towards the river; (3) there is a relationship between students' attitudes and behaviour towards the river; (4) students already have good attitudes and behaviour towards sand mining activities around the river. However, efforts still need to be made to equip students with the knowledge, skills, values and attitudes needed to contribute more to the preservation of the surrounding river environment